Screening of depression in overweight and obese pregnant women and its predictors. Issue 11 (1st October 2019) - Salehi‐Pourmehr, Hanieh; Dolatkhah, Neda; Gassab‐Abdollahi, Nafiseh; Farrin, Nazila; Mojtahedi, Mandana; Farshbaf‐Khalili, Azizeh
Abstract: Aim: The aim of this study was to investigate the screening result of depression and its predictors in overweight and obese pregnant women in second and third trimester of pregnancy. Methods: The present cross‐sectional study was carried out on 232 overweight or obese pregnant women older than 18 years in the second and third trimesters of pregnancy. Edinburgh Postnatal Depression Scale questionnaire, the International Physical Activity Questionnaire and the Food Record were used. Independent t ‐test, Man–Whitney U, Pearson and Spearman correlation test, independent t ‐test, one‐way analysis of variance and, multivariate linear regression were applied for data analysis using spss 21. Results: The results of the study showed that the mean (standard deviation) score of depression was 10.1 (4.4), and it was similar in both overweight and obese women ( P = 0.784). Median (quartile 25–75) of physical activity was 891.0 (495.0–1336.0) metabolic equivalent of task ‐min/week. The total physical activity in obese women was statistically higher than overweight ones ( P = 0.032). In linear regression model, the variables of parity, body mass index, physical activity education, protein, fat, oleic acid, monounsaturated fatty acids, potassium, magnesium, and zinc were the strong predictors of depression, and along with the others explained the 80% of variances. Conclusion: Considering the fact that nearly one‐third of overweight and obese women in the present study were positive for depression screening, it is important to pay attention to strong predictors of depression in these women.